2010
DOI: 10.1177/1074248410372925
|View full text |Cite
|
Sign up to set email alerts
|

Both Mitochondrial KATP Channel Opening and Sarcolemmal KATP Channel Blockage Confer Protection Against Ischemia/Reperfusion-Induced Arrhythmia in Anesthetized Male Rats

Abstract: results of the current study indicate that both mitochondrial K(ATP) channel activation and sarcolemmal K(ATP) channel inhibition exert antiarrhythmic action in male rats. The antiarrhythmic effect of pinacidil is not depend on the sarcolemmal K(ATP) channel opening. These results also indicate that K(ATP) channel modulators show no discernable effect in female rats due to the already low incidence of arrhythmias in females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 35 publications
1
20
0
1
Order By: Relevance
“…Additionally, reperfusion injury may cause the release of metabolites, which may affect resting membrane potential, intracellular Ca 2+ concentrations and ion channel function [44,45]. In the present study, we observed that GA decreases the incidence of I/R injury-induced arrhythmia.…”
Section: Discussionsupporting
confidence: 63%
“…Additionally, reperfusion injury may cause the release of metabolites, which may affect resting membrane potential, intracellular Ca 2+ concentrations and ion channel function [44,45]. In the present study, we observed that GA decreases the incidence of I/R injury-induced arrhythmia.…”
Section: Discussionsupporting
confidence: 63%
“…It has been shown that ATP dependent potassium (K ATP ) channel blockage confers protection against I/Rinduced arrhythmias (23,24). Ketamine inhibits the K ATP channel activity in a concentration-dependent manner in the rat heart (41).…”
Section: Discussionmentioning
confidence: 99%
“…Both thiopental and ketamine+xylazine (K+X) have been used in studies involving experimental cardiology (16)(17)(18)(19)(20)(21)(22)(23)(24). However, there are only a few studies addressing the influence of anesthetics on I/R-induced arrhythmias (7)(8)(9)(10), whilst there has been no comparison between these two commonly used anesthetics (thiopental and K+X) in an in vivo I/R arrhythmia model.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that ATP-sensitive K + channels (K ATP ) play an important role in protecting the heart from ischemic-reperfusion injury [4,5]. The neuroprotective effects of K ATP channels are involved in the mechanisms of many agents that have been shown to be capable of protecting the brain [6].…”
Section: Introductionmentioning
confidence: 99%